Impact of sheep stocking density and breed on behaviour of newly regrouped adult rams - SEC, Engeldal; ., Subandriyo; E, Handiwirawan; RR, Noor (Indonesian Animal Sciences Society, 2013)
Placing animals in cages with certain density and good grouping were two important aspects needed in intensive livestock production system to produce optimal production and animal welfare. The objective of this study was to examine effect of stocking density, breed and elapse of time on behaviour of newly regrouped, unacquainted adult rams from three sheep breeds i.e. Barbados Blackbelly Cross, Local Garut and Composite Garut, as possible factor causing variation in welfare status. Instantaneous scan sampling was used for recording sheep behaviour at three different stocking densities. Thirty-six adult rams were used in this research and divided into three groups (n = 12) on the basis of breed. At each stocking density four rams of the same breed were observed during two consecutive days. The recorded behaviours were agonistic-, self-care-, exploratory-, aberrant-, mating-, locomotive- and standing behaviour. The results showed that during the entire experiment agonistic behaviour was observed at the highest frequency. Stocking density was found to have a significant effect on exploratory-, locomotive- and standing behaviour. The effect of breed was found to cause significant differences in agonistic-, self-care-, aberrant- and mating behaviour. Significant differences were also found between day 1 and day 2 of regrouping for agonistic-, exploratory, self-care- and mating behaviour. It is concluded that the three breeds do differ in their behavioural reactions to different stocking density levels and time needed for adaptation after regrouping. Key Words: Sheep, Stocking Density, Behaviour, Animal Welfare